Fashion political discourses: the collective Estileras, a semiotic analysis (ModaPalavra e-periódico, 2020)
Fashion is a place of production of meaning in which socialvalues are concretized plastically, enabling the transmissionof the most varied and often antagonistic discourses. In thisway several social groups are constituted with contestingnarratives or reaffirming hegemonic values and tendencies,confirmed plastically in the adopted dress systems. In thewake of this thought we aim to analyze the discursiveresources used by the collective Estileras on its page inasocial media. This collective is positioned as a“place”forexperimentation and transgression of dress norms sanctionedby contemporary society. The theoretical framework ofDiscursive Semiotics, developments in sociosemiotics andMichel Foucault's notions of power will be adopted in order toaccount for the complexity of the verb-visual discoursesexposed by the collective.
Keywords: fashion; politics; semiotics; social media